Redes sociales, agenda noticiosa y línea editorial durante hechos violentos de las protestas de 2017 en Venezuela (2021)
Social networks have become a mechanism for information, recreation, and opinion for users of this type of virtual platforms; precisely, these are the three functions of traditional social communication. Networks are also a tool that the media takes into account when deciding what is the news of the moment. The study revolved around the prevailing news agenda during the 2017 protests in Venezuela based on social networks and supported by journalistic genres, as well as the relationship between human dignity and the way violent events with fatalities were reported. The newspapers El Universal and El Nacional, in their digital version, were studied by means of precision cards in the news related to 7 events involving fatal victims of the protests. It is concluded that, in some information released by these newspapers, some tweets were quoted, and photos and videos that had circulated in the networks were posted. Furthermore, in some of the cases studied, these media spread videos and photographs of the events that reproduced the moment in which the victims died, which defines a sensationalist, commercial and disrespectful news agenda.